Description of the male of the coprophagous moth fly Psychoda serraorobonensis Bravo, Cordeiro & Chagas, 2006 (Diptera, Psychodidae) - Camico, Jéssica L.; Cordeiro, Danilo Pacheco; Lima, Dayana Andrade de (Instituto de Ecología, A.C., 2018)
In the diverse genus Psychoda, a great number of species are described based only on one sex, mainly for the difficulties of sexual association in this taxon. Immatures of coprophagous moth flies were captured on a sample of cow dung left exposed during five days at Reserva Ducke (Manaus, Brazil), in the Brazilian Amazon. The presence of Psychodidae larvae was confirmed with a stereomicroscope and the material was kept resting at room temperature until the emergence of adults. Male and females of Psychoda serraorobonensis Bravo, Cordeiro & Chagas, 2006 were obtained and associated by the morphology of the immatures and adults. The male of P. serraorobonensis is herein described and illustrated and the distribution of this species in Brasil is updated. This is the first data about the feeding habits of this species.